1999
DOI: 10.1083/jcb.146.4.777
|View full text |Cite
|
Sign up to set email alerts
|

Sid2p, a Spindle Pole Body Kinase That Regulates the Onset of Cytokinesis

Abstract: The fission yeast Schizosaccharomyces pombe divides by medial fission through the use of an actomyosin contractile ring. Precisely at the end of anaphase, the ring begins to constrict and the septum forms. Proper coordination of cell division with mitosis is crucial to ensure proper segregation of chromosomes to daughter cells. The Sid2p kinase is one of several proteins that function as part of a novel signaling pathway required for initiation of medial ring constriction and septation. Here, we show that Sid2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
228
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(235 citation statements)
references
References 49 publications
6
228
0
1
Order By: Relevance
“…It should be noted that medial accumulation of the tER and Golgi compartments did decrease upon longer incubation at the restrictive temperature. This might be attributed to the fact that SIN functions in maintaining the actomyosin ring throughout anaphase and cytokinesis Sparks et al, 1999) and therefore is essential for ensuring the continuous localization of the secretory compartments to the site of septation. To confirm that the SIN pathway activity was not essential for the initial secretory machinery recruitment but was required for the maintenance of its polarization state, we performed the time-lapse imaging of sid2-250 mutant cells expressing GFP-tagged secretory pathway marker proteins and Uch2p-mCherry, growing either at the permissive temperature of 24°C or after a 1-h shift to the restrictive temperature of 36°C (Supplementary Figure 5).…”
Section: The Septation Initiation Network Is Required For Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that medial accumulation of the tER and Golgi compartments did decrease upon longer incubation at the restrictive temperature. This might be attributed to the fact that SIN functions in maintaining the actomyosin ring throughout anaphase and cytokinesis Sparks et al, 1999) and therefore is essential for ensuring the continuous localization of the secretory compartments to the site of septation. To confirm that the SIN pathway activity was not essential for the initial secretory machinery recruitment but was required for the maintenance of its polarization state, we performed the time-lapse imaging of sid2-250 mutant cells expressing GFP-tagged secretory pathway marker proteins and Uch2p-mCherry, growing either at the permissive temperature of 24°C or after a 1-h shift to the restrictive temperature of 36°C (Supplementary Figure 5).…”
Section: The Septation Initiation Network Is Required For Maintenancementioning
confidence: 99%
“…Sid2p is the downstream effector kinase of SIN signaling Sparks et al, 1999), and loss of its activity leads to septation failure. Using elutriation, we synchronized cells in the manner described above and observed the localization of Sec24p-GFP, Anp1p-GFP, and Sec72p-GFP in anaphase cells ( Figure 4, E, F, and G, respectively) also expressing the nuclear envelope marker, Uch2p-mCherry, at both 24 and 36°C.…”
Section: The Septation Initiation Network Is Required For Maintenancementioning
confidence: 99%
“…The recruitment of Myo2 to the CAR must be coordinated with the signal transduction pathway leading to septum formation, the septation initiation network. This includes a number of protein kinases, Plo1 (Okhura et al, 1995;Bahler et al, 1998a;Mulvihill et al, 1999), Cdc7 (Fankhauser and Simanis, 1994), Sid 1 (Guertin et al, 2000), and Sid 2 (Sparks et al, 1999), and their associated regulators (reviewed in Gould and Simanis, 1997;Le Goff et al, 1999;Balasubramanian et al, 2000). Any or all of the above are potential fission yeast myosin II heavy chain kinases.…”
Section: Discussionmentioning
confidence: 99%
“…At the heart of this signal transduction pathway are three protein kinases, Cdc7, Sid1, and Sid2 (Fankhauser and Simanis, 1994;Sparks et al, 1999;Guertin et al, 2000) and their activating GTPase Spg1 (Schmidt et al, 1997). The timing of Spg1 activation is determined by a two-component GTPase-activating protein consisting of Cdc16 and Byr4 (Furge et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the lack of dependencies in localization, the occurrence of cells with SIN phenotype in pdk1⌬ cultures suggests that Pdk1p might modulate SIN function positively. In particular, it is interesting to note that Sid2p is related to members of the AGC family of kinases (Sparks et al, 1999;Tamaskovic et al, 2003) which are known to be regulated by PDK1 family members (Belham et al, 1999). However, the finding that SIN proteins participate in correcting defects associated with the cell division apparatus (Le Goff et al, 1999;Liu et al, 1999;Mishra et al, 2004) might provide an alternate explanation to the observed synthetic lethality between pdk1⌬ and SIN mutants.…”
Section: Discussionmentioning
confidence: 90%